2015
DOI: 10.1016/j.annemergmed.2014.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Reduced-Dose Computed Tomography for Ureteral Stones in Emergency Department Patients

Abstract: Study objective-Reduced-dose computed tomography (CT) scans have been recommended for diagnosis of kidney stone but are rarely used in the emergency department (ED) setting. Test characteristics are incompletely characterized, particularly in obese patients. Our primary outcome is to determine the sensitivity and specificity of a reduced-dose CT protocol for symptomatic ureteral stones, particularly those large enough to require intervention, using a protocol stratified by patient size.Methods-This was a prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 56 publications
1
45
0
Order By: Relevance
“…In these cases, we made attempts to communicate with the publishing author to request access to the TP/TN/FP/FN data per patient. This resulted in 12 articles for inclusion in the review [8, 16, 25-34]. Flow chart shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In these cases, we made attempts to communicate with the publishing author to request access to the TP/TN/FP/FN data per patient. This resulted in 12 articles for inclusion in the review [8, 16, 25-34]. Flow chart shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Studies were separated into LD and ULD CT groups, based on the mean radiation dose (mSv). Of these, 4 studies assessed LD CT KUB, including a total of 475 patients [25-28] and 8 studies looked at ULD CT KUB including a total of 1,054 patients [8, 16, 29-34]. Also, 2 of the studies in this category reported TP/TN/FP/FN data from multiple scan reviewers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…23 Reduced-dose CT is recommended by the American College of Radiologists when symptomatic stone is suspected. 24 However, less than 2% of CT scans for renal colic in the United States are conducted with a reduceddose protocol.…”
Section: Discussionmentioning
confidence: 99%